2000
DOI: 10.1177/025576140003600106
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Winding Road: The Story of Rock Music in Scottish Schools

Abstract: What drives young people to become involved in music making in the secondary school? Changes to the curriculum in Scottish schools over the last three decades have resulted in a marked upturn in the numbers of pupils studying music. The inclusion of a wider range of acceptable instruments for examination purposes has resulted in rock music being accepted as a valid form of music within the curriculum. The paper discusses the growth and development of this phenomenon and the philosophical and practical issues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…6 In a study published in 2000, researchers Charles Byrne and Mark Sheridan reported on three decades of change in music practices in Scottish schools, where the inclusion of a wider range of instruments and musical styles with alternate teaching methods has resulted in a marked upturn in the numbers of students studying music. 7 In research printed in 2006, Göran Folkestad studied different aspects of learning (including the situation, learning style, ownership, and intentionality) in societies outside Western cultures. 8 9 Teachers in this project reported that Musical Futures had a positive effect on student participation and retention, student attitudes, self-esteem, and on-task behavior and that students developed a greater range of musical skills and were able to demonstrate higher levels of musical understanding.…”
Section: Other Alternativesmentioning
confidence: 99%
“…6 In a study published in 2000, researchers Charles Byrne and Mark Sheridan reported on three decades of change in music practices in Scottish schools, where the inclusion of a wider range of instruments and musical styles with alternate teaching methods has resulted in a marked upturn in the numbers of students studying music. 7 In research printed in 2006, Göran Folkestad studied different aspects of learning (including the situation, learning style, ownership, and intentionality) in societies outside Western cultures. 8 9 Teachers in this project reported that Musical Futures had a positive effect on student participation and retention, student attitudes, self-esteem, and on-task behavior and that students developed a greater range of musical skills and were able to demonstrate higher levels of musical understanding.…”
Section: Other Alternativesmentioning
confidence: 99%
“…Although fl ow is conceptualized as peak experience rather than peak performance (see Harmison & Casto, 2012, Chapter 38, this volume, for a fuller discussion), a relationship has been found between fl ow and creativity as a performance outcome in composing (Byrne, MacDonald, & Carlton, 2003;MacDonald, Byrne, & Carlton, 2006). Th ese researchers have also been part of developing applied work in music education based on the fl ow model (see also Byrne & Sheridan, 2000).…”
Section: Flowmentioning
confidence: 99%
“…Flow is a state of inspiration and creativity. Flow should be used to manage the learning environment (Byrne & Sheridan, 2000). In this context, the concept of flow as optimal experience and intrinsic motivation are rooted in the desire to understand the activity that promote human creativity.…”
Section: Introductionmentioning
confidence: 99%
“…The promotion of creativity should be a need for schools as a central part of their educational mission (Freedman, 2010).Teachers have to make possible the creation of optimal conditions that will increase the likelihood that in the students will occur creative expressions. Byrne & Sheridan (2000) suggest that a powerful reflective tool for teachers can be developed using the flow model. Such a tool would be valuable to teachers in initiating, planning, monitoring, regulating and assessing learning.…”
Section: Introductionmentioning
confidence: 99%